Knowledge of opposition attacking tendencies on volleyball blocking - Luis-del Campo, V.; Cabeza, E.; Damas, J. S. (Revista Internacional de Medicina y Ciencias de la Actividad Física y del Deporte, 2022)
The aim of the study was to investigate the effects of providing probabilistic information, obtained from video-performance analytics on passing direction tendencies in opposing volleyball setters, on blocking performance in a high skilled female volleyballer. Data on reaction times, decision-making and quality of movement execution of the skilled blocker were analyzed during 1117 blocking actions in 18 competitive matches, before and after receiving information from the passing tendencies of opposition setters. Results revealed that the blocker reacted significantly earlier in those matches when she received information about opposition pass direction tendencies. No effects of contextual information were found for the blocker´s decisions and quality of movement execution. These results reinforced the use of probabilistic information as a competitive strategy for initiating an early preparatory response to the blocking action in high-skill levels of volleyball.